Peningkatan Pengetahuan Kebencanan Di Desa Munggur Kecamatan Andong Kabupaten Boyolali - Dewi, Ratih Puspita; Wibowo, Yunus Aris; Widiyatmoko, Wahyu; Rahma, Aditya Nur; Kesumaningtyas, Mayang Arum (LOSARI DIGITAL, 2024)
Natural disaster that have occurred in several regions in Indonesia in recent years have increased public attention to disasters. In addition in disaster caused by endogenous energy, disaster in Indonesia are also caused by exogenous forces such as disasters related to hydrometeorological conditions, including tornadoes, drought, floods, and fires. Munggur Villaged in Andong District Boyolali Regency has the potential for drought, tornado, and fire disasters. However, information regarding these disasters is minimal received, so it is necessary to increase understanding of the concept of disaster and disaster mitigation to support disaster risk reduction. The aim of this activity was to increase the understanding about the concept of disaster and disaster mitigation. The method of implementation was by conducting disaster and mitigation socialization to residents of Munggur Village. Based on the result of this community service implementation, it was found that there was an increase in understanding of the concept of disaster and disaster mitigation. However, Further socialization or training is needed to strengthen the understanding and skills of the residents.